Enhancement of physical preparedness of athletes with visual impairments by adaptive sports - Mariia Roztorhui; Alina Perederiy; Yuriy Briskin; Khrystyna Khimenes; Olexandr Tovstonoh (University of Banja Luka, Faculty of physical education and sport, 2019)
The analyses of existent scientific knowledge of taking into account level of vision loss at the construction of sportsmen's preparation in adaptive sport testifies about lack of information on the extent of adaptive sports training impact on the level of physical preparedness of people of visual impairment. The aim of the research is to determine the influence degree of adaptive sports training on the physical preparedness of people with visual impairments. Theoretical analysis, pedagogical observation, pedagogical experiment, mathematical and statistical methods were applied. 34 people with visual impairments took part in our research. It has been established that the level of vision loss of people with visual impairment affects the indicators of physical preparedness. There were found significant differences in the level of speed development, flexibility and coordination the blind in comparison with indicators of people with severe visual impairment, and people with moderate visual impairment before and after experiment. As a result of the experiment, there was a significant increase in the indicators of all tests for people with visual impairment. It's indicating the positive impact of adaptive sports training on their physical preparedness. The obtained results indicate that there is a relationship between the level of vision loss of people with visual impairment and the impact of adaptive sports training on their physical preparedness.